Editorial - Gonzalo D. Veiga; Alfonsina Tripaldi (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In our initial statement last year we stressed a few objectives that we considered crucial for the future development of the Latin American Journal of Sedimentology and Basin Analysis and we have been actively working in that regard since we took charge as part of the editorial team in order to make some of them possible. Some really good news have risen in the past months concerning the evolution and current situation of LAJSBA that we want to share with the Latin American sedimentological community.